Study on UV-light-induced absorption in LiNbO3：Fe, Co crystal - 陈洪建 师丽红 阎文博 陈贵锋 李养贤 (Chinese physics B, 2010)
In this paper, the temporary UV-light-induced absorption in LiNbO3：Fe, Co crystal is investigated for different UV intensities. It is found that the sensitizing process in LiNbO3 ：Fe, Co can be considered as a combination of two sub-processes with different time constants. Based on the lattice structure and the photochromic mechanism of the material, the two sub-processes are suggested to arise from electron transfer from O^2- to Fe^3＋ through two paths with different distances. The two-colour recording experiment in LiNbO3：Fe, Co is also preformed by using UV and green light as gating and writing beams respectively. High sensitivity is obtained in the recording, which is considered as the consequence of direct charge transfer from O^2- to Fe^3＋.